A Mixed-Methods Investigation of the Motivations, Goals, and Aspirations of Male and Female Academic Medical Faculty. (August 2016) - Jones, Rochelle DeCastro; Griffith, Kent A.; Ubel, Peter A.; Stewart, Abigail; Jagsi, Reshma
Abstract : Purpose: Understanding the goals and aspirations of the physician–scientist workforce can inform policies to promote retention. The authors explored gender differences therein, given women's increasing representation. Method: In 2010–2011, the authors qualitatively analyzed interviews with 100 former recipients of National Institutes of Health career development awards and 28 of their mentors. They also compared survey responses of 1, 267 clinician–investigators who received these awards from 2006 to 2009, using logistic regression to evaluate gender differences after adjusting for other characteristics. Results: Interview participants described relatively consistent career goals, including scientific contribution and desire to positively affect lives through research, clinical care, and teaching. For many, the specific ways they sought to achieve and measure goal attainment evolved over time. Survey respondents endorsed a goal of publishing high-quality research with highest frequency (97.3%, no significant gender difference). Women were more likely to endorse the importance of balancing work and other activities (95.5% vs. 90.5%, P < .001). There were no significant gender differences in the importance of patient care (86.6%), teaching (71.6%), or publishing prolifically (64.9%). Men were more likely than women to consider salary (49.4% vs. 41.8%, P < .001), reputation (84.2% vs. 77.6%, P = .004), and leadership positions (38.9% vs. 34.3%, P = .03) important. Conclusions: In an elite research-oriented sample, gender differences in initial aspirations were generally limited. Gender differences in career outcomes in such groups are unlikely to exclusively result from different baseline aspirations. Goals appear to evolve in response to challenges experienced. Abstract : Supplemental Digital Content is available in the text.